Exploring the developmental outcomes of service-learning in Higher Education for partner organisations : an exploratory study of two modules at Stellenbosch University - Leslie, Mike (M. C.) (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Sociology and Social Anthropology))--University of Stellenbosch, 2010.